Effect of heat treatment and storage conditions on mead composition - Kahoun, David; Řezková, Soňa; Královský, Josef (Elsevier Science, 2017)
The effects of heat treatment and storage conditions on the composition of pure mead (honey wine) made from only honey and water were investigated. Heat treatment experiments were performed at 7 different temperatures ranging from 40 degrees C to 100 degrees C with 10 degrees C increments for 60 min. Storage condition experiments were performed at room temperature (20-25 degrees C) in daylight without direct sunlight and in darkness in a refrigerator at 4 degrees C for 1, 2, 4 and 12 weeks. The parameters evaluated were phenolic compounds, peak area of unidentified compounds, 5-hydroxymethylfurfural content and antioxidant capacity. Significant changes in compound content were observed in the case of 6 identified compounds and 9 unidentified compounds. However, the antioxidant activity was not affected by the heat treatments or storage at room temperature.
Vliv teploty zpracování a skladovacích podmínek na složení medovin
Keywords: mead; phenolic compounds; 5-Hydroxymethylfurfural; antioxidant activity; heat treatment; storage conditions; HPLC; electrochemical detection; medovina; fenolické sloučeniny; 5-Hydroxymethylfurfural; antioxidační aktivita; tepelné zpracování; podmínky sladování; HPLC; elektrochemická detekce